Authigenic 10Be/9Be ratio on surface sediments in the Arctic Ocean - Agathe Ollive; Florian Adolphi; Jens Matthiessen; Walter Geibert; Michael Alscher; Konstanze Stübner; Johannes Lachner; Martin Frank (PANGAEA, 2025)
This dataset contains geochemical measurements from surface sediments collected across the Arctic Ocean, including the Kara Sea, Laptev Sea, and Eurasian Basin. It includes concentrations of authigenic 10-Beryllium (10Be) and 9Be derived from Fe-Mn oxide leachates, 10Be/9Be ratios, with associated uncertainties (in %). The samples used were retrieved during several cruises, mainly from Box corers and MUC. Sample storage does not affect the quality of our measurement. Before beryllium measurement, the sediment was freeze-dried and ground. The beryllium extraction and purification was made following Loftfield et al., (2024) method. The dataset spans environments from continental shelves to the deep basin, providing a framework to assess the spatial variability of beryllium cycling across the Arctic Ocean. This dataset supports the interpretation of modern processes controlling the 10Be/9Be proxy in marine sediments and its potential use in paleoceanographic reconstructions.